2005
DOI: 10.1097/01.sap.0000164538.72375.93
|View full text |Cite
|
Sign up to set email alerts
|

Keloid or Hypertrophic Scar

Abstract: Keloid and hypertrophic scars are 2 types of excessive scarring observed clinically that require different therapeutic approaches. The clinical course and physical appearance define keloids and hypertrophic scars as separate entities; however, they are often confused because of an apparent lack of morphologic differences. Nevertheless, clinical differences between hypertrophic scars and keloids have long been recognized by plastic surgeons and dermatologists. Yet, translating these differences into morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
57
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(61 citation statements)
references
References 34 publications
0
57
1
Order By: Relevance
“…They are usually of inferior functional qualities and cause aesthetical dissatisfaction. Most studies have focused on pathologic scars, typically including hypertrophic scars and keloids, due to their pruritic, painful, and severely disfiguring symptoms [2][3][4]. However, published literatures have also shown that even considered minor scars have significant psychological impact on patients and impair the quality of life, irrespective of normal or pathologic scars [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…They are usually of inferior functional qualities and cause aesthetical dissatisfaction. Most studies have focused on pathologic scars, typically including hypertrophic scars and keloids, due to their pruritic, painful, and severely disfiguring symptoms [2][3][4]. However, published literatures have also shown that even considered minor scars have significant psychological impact on patients and impair the quality of life, irrespective of normal or pathologic scars [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fact that the etiology of hypertrophic scar formation has not been fully delineated, clinical management remains problematic [1]. Numerous treatments are currently available, including surgical excision, steroid injection, radiation therapy, laser and pressure therapy, but these methods cannot always provide good therapeutic results.…”
Section: Introductionmentioning
confidence: 99%
“…They show strong positive familial association and are seen more often in young age group patients. The incidence of keloids is about 15 times greater in dark skin individuals than in whites 1,2 . Genetic associations for the development of abnormal scars have been found for HLA-B14, HLA-B21, HLA-BW16, HLA-BW35, HLA-DR5, HLA-DQW3, and blood group A.…”
Section: Introductionmentioning
confidence: 99%
“…The term 'keloid' means 'Crab Claw' was first coined by Alibert in 1817. 1,2 Ear pinna keloids occur in about 5-15 % of humans from manual trauma and blunt perichondrial trauma. Both sexes are affected, but the incidence is higher in women.…”
Section: Introductionmentioning
confidence: 99%